IMPLEMENTATION OF THE MARKETING TOOLKIT OF STRATEGIC MANAGEMENT OF INNOVATIONS IN THE PROCESS OF ENSURING THE EFFICIENCY OF THE MACHINE-BUILDING ENTERPRISE’S FOREIGN ECONOMIC ACTIVITY - SHPILEVA, Vira; POLYOVA, Nataliya; SHPYLOVYI, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article emphasizes the importance of strategic innovation management in the process of ensuring the effectiveness of the enterprise’s foreign economic activity. The necessity of implementing marketing tools and its role in the strategic management of innovative and foreign economic processes of the enterprise is highlighted. The obtained results of the analysis of the latest research and publications allowed us to conclude that modern trends have led to changes in scientific interests regarding the study of priority areas of enterprise activity and prerequisites that determine the success of their development. When ensuring the efficiency of foreign economic activity, it is appropriate for machine-building enterprises to develop a system of strategic management of innovations. The list of conditions that expand the scope of application of marketing tools in strengthening the innovative activity of the machine-building enterprise in the system of foreign economic activity is highlighted: formation of a motivational environment; implementation of Industry 4.0 technologies; use of alternative sources of investment; development of the potential of innovative activity; information provision and database formation; expansion of foreign economic relations; development of communications and creation of digital platforms; development of organizational culture. The marketing toolkit should take into account the influence of globalization trends, changes in the environment of resource provision, structural transformations of the national economy, etc., which allows to successfully solve the tasks and create the necessary prerequisites for strengthening the innovative activity and development of the enterprise’s foreign economic relations. The advantages of marketing tools and the consequences of refusing their implementation for machine-building enterprises in the development of innovative and foreign economic activities are given.